Enhancement of the Sub-Band-Gap Photoconductivity in ZnO Nanowires through Surface Functionalization with Carbon Nanodots - Cammi, Davide; Zimmermann, Kseniia; Gorny, Rene; Vogt, Angelina; Dissinger, Frank; Gad, Alaaeldin; Markiewcz, Nicolai; Waag, Andreas; Prades, Joan Daniel; Ronning, Carsten; Waldvogel, Siegfried R.; Voss, Tobias (Journal of Physical Chemistry C, 2018)
We report on the surface functionalization of ZnO nanowire (NW) arrays by attachment of carbon nanodots (C-dots) stabilized by polyethylenimine. The photoconductive properties of the ZnO NWs/C-dots devices were investigated under photoexcitation with photon energies below and above the ZnO band gap. The results indicate an increased photoresponse of the functionalized devices in the visible spectral range, as well as enhanced UV photoconductivity. This is attributed to the fast injection of photoexcited electrons from the C-dots into the conduction band of the ZnO NWs, and the subsequent slower desorption of molecular species from the NW surface, which reduces the surface depletion region in the NWs. The surface functionalization of the ZnO NWs with carbon nanodots also impacts the dynamics of the photocurrent decay, inducing a slower relaxation of the photogenerated charge carriers.
CRIS-Team Scopus Importer:2023-04-20